Reactivation of natural fractures network by hydraulic fracturing - Alvarez, Leidy Laura; Beserra, Leila; Guimarães, Leonardo; Manzoli, Osvaldo [UNESP] (EDP Sciences, 2020)
Modelling the process of induced fracture initiation, propagation and interaction with natural fractures is a very challenged task. Significant progress has been made in recent years in the development of complex fracture models to address the needs for more suitable design tools than the conventional planar fracture models. However, some aspects of this complex process are not still fully understood in terms of their impact or importance to the overall fracture geometry, or the complexity of simulating them is beyond the current modelling capabilities or requires computation effort that is not practical for engineering purpose. A technique that has been developed to represent the process of fracture propagation is the Continuous Approximation of Strong Discontinuities, which introduces a special kinematics, capable of representing the process of degradation of the material. One way to implement this approximation is to introduce the effects of a very narrow band of localized deformations within the existing finite elements. In this paper was used a finite element procedure that performs numerical analysis of fluid flow in a deformable porous media in a fully coupled scheme. In this analysis the propagation of the hydraulic fracture occurs specially along the pathway of the natural fractures, due to their lower tensile strength and greater permeability.